Changes in Visual and Olfactory Cues in Virus-Infected Host Plants Alter the Behavior of Bemisia tabaci - Zhang, Zelong; Zhang, Beibei; He, Haifang; Yan, Minghui; Li, Jingjing; Yan, Fengming (Frontiers in Ecology and Evolution, 2022)
The cucurbit chlorotic yellows virus (CCYV) has caused serious damage to melon crops in many countries in recent years. This plant virus is exclusively transmitted by the whitefly Bemisia tabaci (Gennadius) in a semi-persistent mode. Previous studies have shown that both persistent and non-persistent viruses can affect orientation and performance of insect vectors, through changing host phenotype or directly interacting with insect vectors to facilitate spread of viruses. However, how CCYV affects host-plant selection by B. tabaci has not been reported. Here, we investigated visual and olfactory preferences of B. tabaci between healthy and CCYV-infected host plants Cucumis sativus (Cucurbitaceae). Volatile profiles of healthy and CCYV-infected C. sativus plants were analyzed by using gas chromatography-mass spectrometry (GC-MS). In choice assay, whiteflies preferred to settle on CCYV-infected C. sativus seedlings. However, the concentrations of total volatiles and terpenes in C. sativus plants decreased after CCYV infection. Interestingly, in Y-tube assay and vision preference test, whitefly B. tabaci adults showed significant visual preference to CCYV-infected host but showed olfactory preference to healthy plants. These results indicated that CCYV infection in plants differently affected visual and olfactory behaviors of vector whiteflies in host plants and implied that visual cues could play a more important role than olfactory cues in whiteflies in locating CCYV-infected host plants.